PHARMACEUTICAL NIOSOMES DRUG DELIVERY: A COMPLETE REVIEW OF NEW DELIVERY SYSTEM - Maurya, Priyanka; Shalini; Mishra, Jai Narayan; Kushwaha, Ashutosh (IJRDO-Journal of Applied Science, 2022)
Over the past ten years, people working in the field of drug delivery systems have become increasingly interested in designing vesicles as a tool to improve drug delivery. A hydrating mixture of cholesterol and nonionic surfactants forms niosomes, which are vesicles. Liposomes, microspheres, engineering science,small emulsions, antibody loaded drug delivery , magnetic microcapsules,implantable pumps, and niosomes are just a few of the unique methods employed to administer these medications. There are two requirements before designing and developing a novel drug delivery system (NDDS). It must first spread the medication at a preset rate and then release an amount of medication at the site of action that is therapeutically efficacious. These requirements cannot be satisfied by conventional dose forms. In essence, niosomes are non-ionic surfactant-based vesicles in which a group of surfactant macromolecules forms a bilayer to form a membrane that entirely seals off an aqueous solution of solute. Targeted medication delivery is made possible by the reasonable circulation persistence of niosomes. An overview of niosome preparation techniques, niosome kinds, characterisation, and applications is also included in this paper. Due to qualities including improved drug penetration, local depot for continuous drug release, and a rate-limiting membrane for modulating systemic absorption of pharmaceuticals via the skin, niosomes, vesicular nanocarriers, are gaining a lot of attention as prospective transdermal drug delivery systems. There are a number of theories put up to explain why niosomes can improve medication transfer through the skin. This review aims to provide an exhaustive collection of recent studies in this fascinating field, with special emphasis on the methods used to maximise the potential of niosomes. Niosomal carriers are suitable for the transdermal delivery of a variety of pharmacological agents, including antioxidant, anticancer, anti-inflammatory, antimicrobial, and antibacterial molecules.